Pharmacokinetics of duloxetine self-administered in overdose with quetiapine and other antipsychotic drugs in a Japanese patient admitted to hospital - Koichiro Adachi; Satoru Beppu; Kei Nishiyama; Makiko Shimizu; Hiroshi Yamazaki (BMC, 2021)
Abstract Background Combinations of antidepressant duloxetine (at doses of 40-60 mg/day) and other antipsychotics are frequently used in clinical treatment; however, several fatal and nonfatal cases of duloxetine overdose have been documented. We experienced a patient who had taken an overdose of duloxetine (780 mg) in combination with other drugs in a suicide attempt. Case presentation The patient was a 37-year-old man (body weight, 64 kg) with a history of gender identity disorder and depression. He intentionally took an overdose of duloxetine in combination with three other antipsychotic drugs (18 mg flunitrazepam, 850 mg quetiapine, and 1100 mg trazodone) and was emergently admitted to Kyoto Medical Center. The patient's plasma concentration of duloxetine during ambulance transport was 57 ng/ml, and the level was still as high as 126 ng/mL at 32 h after administration. Duloxetine disappeared most slowly from plasma, in contrast to quetiapine, which was the fastest to clear among the four medicines determined in this patient. The observed concentrations of duloxetine in this overdose patient were generally within the 95% confidence intervals of the plasma concentration curves predicted using a physiologically based pharmacokinetic (PBPK) model. Conclusion Even if more than 1 h (the generally recommended period) has passed after administration of duloxetine in such overdose cases, gastric lavage and/or administration of activated charcoal may be effective in clinical practice up to 6 h because of the typically slow elimination behavior illustrated by the PBPK model. Pharmacokinetic profiles visualized using PBPK modeling can inform treatment decisions in cases of drug overdose for medicines such as duloxetine in emergency clinical practice.